Tingkat Kondisi Fisik Ekstrakurikuler Bola Basket Putra SMAN 2 Pekanbaru - Endrisman, Rony; Jatra, Rices (Indonesian Research Journal on Education, 2023)
The purpose of this study was to determine the Physical Condition Level of Basketball Extracurricular Men’s SMAN 2 Pekanbaru. This type of research is a quantitative descriptive study, the population in this study is all Extracurricular Men’s SMAN 2 Pekanbaru players, totaling 20 people. sampling technique in this study used a total sampling of 20 people. The test instrument used in this study refers to theIndonesian National Sports Committee which consists of a 15-minute (Vo2Max) Kg run test, Push Up, Sit Up, Squat Jump, and 50-meter run. Based on the data processing that has been done with the statistical system for the Babussalam FC soccer team players, the average score is 3.13 with a percentage (of 15,65%). So it can be categorized as the Physical Condition Level of Basketball Extracurricular Men’s SMAN 2 Pekanbaru.